Parallel DNA Extraction From Whole Blood for Rapid Sample Generation in Genetic Epidemiological Studies - Lee, Kiara; Tripathi, Anubhav (Frontiers in Genetics, 2020)
With advances in Next Generation Sequencing (NGS) and genome-wide association studies, large-scale genetic epidemiological studies are becoming more common. These studies require high quality analysis of multiple patient samples, such as blood or saliva. Therefore, to maximize these studies’ impact, minimal sample storage time and less complex extraction of a substantial quantity and purity of DNA or RNA for downstream applications is necessary. Here, a simple microfluidic-based system that performs genomic DNA (gDNA) extraction from human whole blood was developed. To begin, a mixture of blood lysate, paramagnetic beads, and binding buffer are placed into the input well. Then the gDNA-bound paramagnetic beads are pulled using a magnet through a center channel containing a wash buffer to the output well containing elution buffer. This step can be performed manually, but was automated to standardize magnet movement. The gDNA is eluted at 55oC off the chip. This system uses minimal sample handling and equipment, while maintaining gDNA yield when compared to the manual chemagicTM kit (PerkinElmer, Waltham, MA, USA). gDNA quantification techniques including quantitative PCR, spectrofluorimetry, and electrophoresis were used to test the gDNA eluted from the chip following extraction. Bead transport and molecular diffusional analysis were performed for optimization of gDNA elution. This revealed that above a critical mass, the high molecular weight gDNA (>~150kbp and >~49µm) forms complexes with multiple paramagnetic beads (1.5µm in diameter) which blocks its transport through the center channel of the microfluidic chip (150µm in width). To further elucidate the parameters of the DNA-paramagnetic bead aggregate formed, this phenomenon was mathematically modeled and tested. There was no observable transport of inhibitors into the eluate that would greatly affect quantitative PCR, and a sample was successfully prepared for NGS. The microfluidic-based extraction of DNA from whole blood described here is paramount to future work in DNA-based POC diagnostics and NGS library workflows.